EVALUASI SISTIM LAYANAN PERPUSTAKAAN DI SMK KEHUTANAN NEGERI PEKANBARU - Indriyeni, Indriyeni (JURNAL PUSTAKA BUDAYA, 2017)
AbstractThis study aims to determine the evaluation system of library services in the  State Forestry Vocational Pekanbaru 2014 (Seen from the user function teachers, librarians and students). The research used a qualitative descriptive, with data collection through interviews, observation and literature. In conducting the study, the authors equip themselves demgan interview guide. Informants in this study consisted of principals, teachers, librarians and students. Results from this study is that the Evaluation System Library Services Vocational Pekanbaru State Forestry is very efeksien to library service system, although there are still many shortcomings such as in terms of amenities, facilities, service system, operational funds processing, coaching. Correcting deficiencies consists additional operational funds collection and processing, collection. While weighing the  disadvantages consists of completeness library. Besides, it is expected to add human resources master oflibrary  science that can manage and develop the library. Expected future borrowing  and  repayment  system  in  Forestry  SMK Negeri  Pekanbaru  using computerized.Keywords:  Evaluation  of  Library  Service  System  State  Forestry  Vocational PekanbaruAbstrakPenelitian ini bertujuan untuk mengetahui evaluasi sistim layanan di Perpustakaan SMK Kehutanan Negeri Pekanbaru tahun 2014 dilihat dari fungsi pengguna guru, pustakawan dan siswa-siswi. Jenis penelitian yang digunakan deskriftif kualitatif, dengan teknik pengumpulan data melalui wawancara, observasi dan studi pustaka. Informan dalam penelitian ini terdiri dari kepala sekolah, guru, pustakawan dan siswa-siswi. Hasil dari penelitian ini bahwa Evaluasi Sistim Layanan di Perpustakaan SMK Kehutanan Negeri Pekanbaru belum efesien, ini terlihat dari  masih banyak kekurangan seperti dalam hal fasilitas, sarana, sistim layanan, dana operasional pengolahan, dan pembinaan. Mengoreksi kekurangannya terdiri penambahan koleksi dan dana operasional pengolahan, koleksi. Sedangkan menimbang kekurangannya terdiri dari kelengkapan perpustakaan. Disamping itu diharapkan menambah sumber daya manusia yang menguasai ilmu perpustakaan yang bisa mengelola dan mengembangkan perpustakaan. Kedepannya diharapkan sistim peminjaman dan pengembalian di Perpustakaan SMK Kehutanan Negeri Pekanbaru mengunakan komputerisasi.Kata Kunci:  Evaluasi, Sistim Pelayanan, Perpustakaan SMK Kehutanan Negeri Pekanbaru